Literature review: Vitamin D Levels and Perinatal Depression Association - Dyaningratri Azzahra, Pingkan; Sawitri, Brihastami (Jurnal Medis Islam Internasional, 2023)
Background: Vitamin D levels have been linked to psychological symptoms such as anxiety, depression, and impaired cognitive performance. It is found that lower vitamin D levels in early pregnancy are associated with depressive symptoms in perinatal.This study examines the association between vitamin D levels and perinatal depression. This article based on literature source from Pubmed/MEDLINE and Science Direct with keywords: vitamin D levels including 25(OH)D levels or vitamin D deficiency, prenatal, antenatal, and postpartum depression. The discussion of this study will assist readers and health professionals analyze how vitamin D levels in the body affect the incidence of antepartum depression. Results: these are five filtered literature, the journal discusses the relationship between vitamin D levels and antepartum depression. This literature review shows that pregnant women with less than 20 ng/mL vitamin D levels are 3.3 times more at risk than pregnant women with more than 20 ng/mL. Vitamin D plays a role in the process of increasing serotonin synthesis and increasing anti-inflammatory so that it can suppress the increase in pro-inflammatory cytokines that play a role in the incidence of depression. Conclusion: There is a correlation between vitamin D levels and the occurrence of depression during the perinatal period. It can be suggested that pregnant women check their vitamin D levels regularly.